Access versus integration: the benevolent undermining of an Indian desegregation policy. Issue 2 (4th March 2023) - Gilbertson, Amanda; Dey, Joyeeta
ABSTRACT: Efforts to desegregate schools have consistently been undermined by privileged parents finding ways to avoid undesirable schools. In some contexts, a more complex picture is emerging, where 'progressive' privileged parents choose 'diverse' schools but still reproduce segregation. We demonstrate how the desegregation aims of an Indian education policy are similarly undermined by seemingly well-intentioned privileged actors. India's Right to Education Act of 2009 requires private schools to educate disadvantaged children for free. The architects of this policy imagined that it would not only provide access to quality education for disadvantaged children, but also desegregate schools. Beneficiaries of the policy share the policymakers' vision of desegregation. However, various elite and middle-class actors prioritise access over integration, and assert that segregated classrooms may be in the best interests of underprivileged children. This highlights how desegregation policies can fail not just as a result of direct opposition but also through discourses of benevolence.